Management of tetralogy of Fallot in South Africa - Kinsley, Robin H. (SA Heart Journal, 2024)
This issue of the Journal contains 2 papers on the local management of tetralogy of Fallot (TOF). The first comprehensively and frankly reviews the surgical repair of TOF in a state hospital. The detailed text is well complemented by excellent tables and figures. Particularly noteworthy is the complete (100%) early postoperative studies of the severity of pulmonary regurgitation, right ventricular outflow gradients and trans-annular plane systolic excursion (TAPSE), by transthoracic echocardiogram. Under the circumstances, the surgery itself was satisfactory.